Population Pharmacokinetics of Mycophenolic Acid in Renal Transplant Patients: A Comparison of the Early and Stable Posttransplant Stages - Wang, Peile; Xie, Hongchang; Zhang, Qiwen; Tian, Xueke; Feng, Yi; Qin, Zifei; Yang, Jing; Shang, Wenjun; Feng, Guiwen; Zhang, Xiaojian (Frontiers in Pharmacology, 2022)
ABSTRACT: Mycophenolic acid (MPA) is an antimetabolic immunosuppressive drug widely used in solid organ transplantation and autoimmune diseases. Pharmacokinetics (PK) of MPA varies widely inter- and intra-individuals. The aim of this study was to compare the population PK properties of MPA in adult renal transplant patients in the early and stable post-transplant stages and to simulate an optimal dosing regimen for patients at different stages. A total of 51 patients in the early post-transplant period (one week after surgery) and 48 patients in the stable state (5.5-10 years after surgery) were included in the study. In the two-compartment population PK model, CL/F (23.36 L/h vs 10.25 L/h) and V/F (78.07 L vs 16.24 L) were significantly different between the two stages. The dose-adjusted area under the concentration time curve (AUCss,12h/dose) for patients in the early stage were significantly lower than those for patients in the stable state (40.83 ± 22.26 mg·h/L vs 77.86 ± 21.34 mg·h/L; P < 0.001). According to Monte Carlo simulations, patients with 1.0-1.5 mg of mycophenolate mofetil twice daily in the early phase and 0.50-0.75 mg twice daily in the stable phase had a high probability of achieving an AUCss,12h of 30-60 mg·h/L. In addition, limited sampling strategies showed that two 4-point models (C0-C1-C2-C4 and C1-C2-C3-C6) performed well in predicting MPA exposure by both Bayesian estimate and regression equation and could be applied in clinical practice to assist therapeutic drug monitoring of MPA.